Factors influencing metaverse adoption among Korean soldiers - Min Sung Kim; Seongcheol Kim (Acta Psychologica)
The metaverse is gaining attention as a catalyst for innovating digital ecosystems and related businesses; however, it presents both opportunities and risks. This study examines the factors influencing Korean soldiers' intention to use the metaverse, whose activities in the physical world are significantly constrained. An online survey was conducted, and partial least squares structural equation modeling was employed to analyze the research model. The results indicate that the benefits derived from the metaverse, namely usefulness and economic value, impact metaverse adoption, while sacrifice-related factors do not significantly affect metaverse adoption. Concerns about military security significantly decrease the intention to use or recommend the metaverse. Social presence positively affects all four benefit-related variables but not all three sacrifice-related variables. Telepresence plays a significant role in enhancing both perceived benefits and sacrifice factors, except for its influence on economic value and crime concerns. Social presence increases concerns about military security, while telepresence has been found to increase stress related to military life.